Disability and sanctity in the Middle Ages
1 online resource (308 pages).
Keywords: This volume significantly expands current understandings of both disability and sanctity in the Middle Ages. Across the collection, heterogeneous constructions, and experiences, of disability and holiness are excavated. Analyses span the sixth to the fifteenth century, with discussion of holy men and holy women, Western Christian and Buddhist traditions, hagiographic texts, images, and artefacts. Each chapter underscores that disability and sanctity co-exist with a vast array of connotations, not just fully positive or fully negative, but also every inflection in between. The collection is a powerful rebuttal to the notion of the integral relationship of disability-medieval and otherwise-with sin, stigma, and shame. So doing, it recentres medieval disability history as a lived history that merits exploration and celebration. In this way, the volume serves to reclaim sanctity in disability histories as a means to affirm the possibility of radical disability futures.